Endurance Effect of Rasayana Drug “Ashwagandha-Withania Somnifera” in Athletes-A Review Article - Bhushan, Bharat; Singh, Jaram; Sason, Rajveer (International Research Journal of Ayurveda & Yoga, 2022)
Doping drugs or performance-enhancing substances are illicit substances used to improve performance. These substances could be toxic and have a negative effect on athlete’s health. Rasayana therapy can be given to healthy people to boost health and increase strength as well as to sick people to improve their immunological resistance. Researchers have discovered that Ashwagandha and other Rasayana drugs have nootropic (improving cognition and brain function) advantages in addition to immunomodulatory, adaptogenic, antioxidant, anti-aging, nutritional, anabolic, haemopoetic, and anti-ageing characteristics. Numerous herbal blends and other Rasayana treatments are available based on the demands of the individual. Various Research study have been carried out which shows adaptogenic effect of ashwagandha. This paper aims to study endurance effect of ashwagandha through various studies.